1999
DOI: 10.1021/ja992335q
|View full text |Cite
|
Sign up to set email alerts
|

The Photochemistry of trans-ortho-, -meta-, and -para-Aminostilbenes

Abstract: The photochemical behavior of the three positional isomers of trans-aminostilbene is reported and compared to that for unsubstituted trans-stilbene. The absorption spectrum of the para isomer displays a single intense long-wavelength band; however the meta and ortho isomers display two less intense bands as a consequence of configuration interaction. All three isomers are fluorescent and display similar solvent-induced shifts of their fluorescence maxima. The fluorescence rate constant of the para isomer is la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
236
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(257 citation statements)
references
References 54 publications
19
236
2
Order By: Relevance
“…It is known that the C¼C torsion barrier is $3.5 kcal/mol for trans-stilbene [24]. A similar value of 3.6 kcal/mol was also determined for the case of trans-4-aminostilbene (4AS) and its N,N-dimethyl derivative 4DS [54,55]. However, the C¼C torsion barriers are 4.9 and 7.4 kcal/mol for p1H and p1CN, respectively, in hexane [52,56].…”
Section: The N-arylamino Conjugation Effectsupporting
confidence: 54%
See 2 more Smart Citations
“…It is known that the C¼C torsion barrier is $3.5 kcal/mol for trans-stilbene [24]. A similar value of 3.6 kcal/mol was also determined for the case of trans-4-aminostilbene (4AS) and its N,N-dimethyl derivative 4DS [54,55]. However, the C¼C torsion barriers are 4.9 and 7.4 kcal/mol for p1H and p1CN, respectively, in hexane [52,56].…”
Section: The N-arylamino Conjugation Effectsupporting
confidence: 54%
“…The weak D-A electronic coupling in meta-amino systems is sufficient to induce ICT from D to A upon photoexcitation, but once charge separation has occurred the charge delocalization and recombination in the relaxed PICT state becomes inefficient, leading to large dipole moments and low fluorescence rate for the PICT state. This explains not only the longer wavelength of fluorescence maximum (446 vs. 423 nm) but also the longer fluorescence lifetime (11.7 vs. $0.1 ns) for 3AS vs. 4AS in acetonitrile [54]. Note that the excited state deactivation is a game of kinetics: the relatively higher is the rate for a specific decay channel than all the other pathways, the larger is the quantum efficiency for that channel, regardless the absolute value of the rate constants.…”
Section: The Meta-amino and Para Para-diamino Effectsmentioning
confidence: 90%
See 1 more Smart Citation
“…The photoisomerization in linear polyenes is highly regioselective and is much influenced by substitutent, polarity of the medium [28][29][30][31][32][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and dipolar nature of the excited state [74][75][76][77][78]. Various mechanistic models have been proposed to understand the photoisomerization process of retinyl and related polyenes.…”
Section: Cistrans-photoisomerization Of Diphenylpolyenesmentioning
confidence: 99%
“…Substituent can raise or lower the torsional energy barrier and thus the Φ f as well as photoisomerization quantum yield (Φ t-c ) are altered. It is also found that stilbene containing heavy atom/groups (e.g., halogen, nitro) on one of its phenyl rings undergoes photoisomerization from its triplet excited state rather than singlet excited state [65][66][67].…”
Section: Cistrans-photoisomerization Of Diphenylpolyenesmentioning
confidence: 99%